PSYCHOLOGICAL AND EMOTIONAL STATE OF ATHLETES - Urakov Ixtiyor Baxtiyorovich; Avezov Olmos Ravshanovich (American Journals, 2023)
The article describes the idea of the stylistic nature of correcting the psychological and emotional state of athletes.
Keywords: Sports, adolescents, emotions, judges, psychological situations, anatomical, physiological, biological, thinking, puberty, will, sensory organs.